2007
DOI: 10.1007/s10517-007-0246-0
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of vasomotor reaction of cerebral vessels in arterial hypertension

Abstract: We studied vasomotor activity of rat cerebral vessels. Peculiarities of endothelium-dependent reactions of cerebral arteries in induced arterial hypertension were revealed. Quantitative and qualitative relationships between the parameters of the vasomotor apparatus of cerebral arteries and parameters of circulatory homeostasis were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Hence, we detected specific features of the reaction of NO neurons in the studied nuclei of the bulbar vasomotor center in AH. First, most quantitative parameters of the nitroxidergic system were reduced in all cases; this was presumably a cause of hyperactivation of the sympathetic nervous system and moderate elevation of blood pressure observed in patients with early forms of the disease [2]. Second, more pronounced shifts in the STN parameters were detected in comparison with other nuclei.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Hence, we detected specific features of the reaction of NO neurons in the studied nuclei of the bulbar vasomotor center in AH. First, most quantitative parameters of the nitroxidergic system were reduced in all cases; this was presumably a cause of hyperactivation of the sympathetic nervous system and moderate elevation of blood pressure observed in patients with early forms of the disease [2]. Second, more pronounced shifts in the STN parameters were detected in comparison with other nuclei.…”
Section: Resultsmentioning
confidence: 84%
“…Activity of neuronal NO synthase is reduced significantly in the majority of nuclei in patients with early forms of arterial hypertension, while the content of NO-positive cells was only slightly changed. More pronounced changes in this parameter were detected in the solitary tract nuclei in comparison with the reticular formation nuclei, which had efferent relationships with the intermediate lateral spinal nucleus.Experimental studies [1,2] showed that molecular regulators synthesized in the nervous tissue, including NO, are involved in neurogenic mechanisms of arterial hypertension (AH) formation. At the central level, NO inhibits sympathetic activity and reduced blood pressure [2,10,12].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that the role of NO in this process is mainly associated with endothelium-dependent vasomotor control mechanisms [1][2][3]. However, the presence of nitroxidergic neurons (NOneurons) in the medulla oblongata was hypothesized, where they can be involved into central mechanisms of blood pressure control [4,7].…”
mentioning
confidence: 99%